Effect of Loan Portfolio Diversification on Financial Performance: Evidence from Licensed Commercial Banks in Sri Lanka - Sazna MIF (P3M Politeknik Negeri Banjarmasin, 2025)
This study investigates the impact of loan portfolio diversification on the financial performance of licensed commercial banks in Sri Lanka from 2014 to 2023. While portfolio theory emphasizes diversification as a tool to reduce risk, its effect in the Sri Lankan context remains unclear. The study distinguishes between product-wise and sector-wise diversification to address this gap. Secondary data from 13 domestic licensed commercial banks were analyzed using purposive sampling. Loan portfolio diversification was measured through the Herfindahl–Hirschman Index (HHI), with Pearson’s correlation and panel data regression applied. Control variables included capital adequacy, non-performing loans, liquidity, and bank size. Results reveal that product-wise diversification negatively affects financial performance, while sector-wise diversification shows a significant positive effect. Capital adequacy ratio and non-performing loan ratio negatively influence performance, whereas liquidity has an insignificant positive impact. Bank size demonstrates a significant negative effect. Findings suggest that banks can improve profitability through product concentration while enhancing stability via sector diversification, offering useful insights for managers and regulators.